Does the Janani Suraksha Yojana cash transfer programme to promote facility births in India ensure skilled birth attendance? A qualitative study of intrapartum care in Madhya Pradesh - Sarika Chaturvedi; Ayesha De Costa; Joanna Raven (Taylor & Francis Group, 2015)
Background: Access to facility delivery in India has significantly increased with the Janani Suraksha Yojana (JSY) cash transfer programme to promote facility births. However, a decline in maternal mortality has only followed secular trends as seen from the beginning of the decade well before the programme began. We, therefore, examined the quality of intrapartum care provided in facilities under the JSY programme to study whether it ensures skilled attendance at birth. Design: 1) Non-participant observations (n=18) of intrapartum care during vaginal deliveries at a representative sample of 11 facilities in Madhya Pradesh to document what happens during intrapartum care. 2) Interviews (n=10) with providers to explore reasons for this care. Thematic framework analysis was used. Results: Three themes emerged from the data: 1) delivery environment is chaotic: delivery rooms were not conducive to safe, women-friendly care provision, and coordination between providers was poor. 2) Staff do not provide skilled care routinely: this emerged from observations that monitoring was limited to assessment of cervical dilatation, lack of readiness to provide key elements of care, and the execution of harmful/unnecessary practices coupled with poor techniques. 3) Dominant staff, passive recipients: staff sometimes threatened, abused, or ignored women during delivery; women were passive and accepted dominance and disrespect. Attendants served as 'go-betweens' patients and providers. The interviews with providers revealed their awareness of the compromised quality of care, but they were constrained by structural problems. Positive practices were also observed, including companionship during childbirth and women mobilising in the early stages of labour. Conclusions: Our observational study did not suggest an adequate level of skilled birth attendance (SBA). The findings reveal insufficiencies in the health system and organisational structures to provide an 'enabling environment' for SBA. We highlight the need to ensure quality obstetric care prior to increasing coverage of facility births if cash transfer programmes like the JSY are to improve health outcomes.